2006
DOI: 10.1002/j.2161-0045.2006.tb00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Efficacy, Perceptions of Barriers, Vocational Identity, and the Career Exploration Behavior of Latino/a High School Students

Abstract: This study explored the potential relationship between the social cognitive variables of career decision-making self-efficacy and perceptions of barriers and the outcome variables of vocational identity and career exploration behaviors in a sample of 128 urban Latino/a high school students. The results indicated that higher levels of career decision-making self-efficacy were related to both a more differentiated vocational identity and a greater engagement with career exploration tasks. Perception of fewer bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
104
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 27 publications
12
104
1
2
Order By: Relevance
“…The predictive utility of outcome expectations, supports, and personality variables (e.g., neuroticism, extraversion) varied over grades and time periods. Other researchers have also found CDSE (Gushue, Clarke, Pantzer, & Scanlan, 2006) and career search seif-efficacy (Solberg, Good, Fischer, Brown, & Nord, 1995) to be related to students' engagement in exploratory activities. Choi et al's (2012) meta-analysis indicated that CDSE yields moderate to large bivariate correlations with certain other social cognitive variables (outcome expectations, peer support) and with career indecision.…”
Section: Two Relevant Applications: Research On Career Exploration Anmentioning
confidence: 92%
“…The predictive utility of outcome expectations, supports, and personality variables (e.g., neuroticism, extraversion) varied over grades and time periods. Other researchers have also found CDSE (Gushue, Clarke, Pantzer, & Scanlan, 2006) and career search seif-efficacy (Solberg, Good, Fischer, Brown, & Nord, 1995) to be related to students' engagement in exploratory activities. Choi et al's (2012) meta-analysis indicated that CDSE yields moderate to large bivariate correlations with certain other social cognitive variables (outcome expectations, peer support) and with career indecision.…”
Section: Two Relevant Applications: Research On Career Exploration Anmentioning
confidence: 92%
“…Dozens of studies have demonstrated that, for undergraduate students, feeling confident about implementing one's career decisions is linked with a host of positive vocational outcomes, including career decidedness, career commitment, perceptions of barriers, a more established vocational identity, occupational aspirations, and work hope (Chung, 2002;Guay, Senécal, Gauthier, & Fernet, 2003;Gushue, Clarke, Pantzer, & Scanlan, 2006;Juntunen & Wettersten, 2006;Patton & Creed, 2007). Additionally, CDSE has been linked with academic/major satisfaction (Dahling & Thompson, 2013;Duffy, Allan, & Dik, 2011;Komarraju, Swanson, & Nadler, 2014;Nauta, 2007), major incongruence (Shin, Steger, & Lee, 2014), and all four components of career adaptability Hou, Wu, & Liu, 2014).…”
Section: Career Decision Self-efficacymentioning
confidence: 93%
“…For example, researchers have reported that career-related self-efficacy was positively related to career-related outcome expectations among samples of Latino students (Fouad & Smith, 1996;Gushue, 2006), and that both in turn positively influenced academic and career interests in math and science-related fields among a sample of mainly Hispanic middle school students (Fouad & Smith, 1996). In other studies, high career decision-making self-efficacy was associated with nontraditional career goals for a sample of Black and Latina ninth grade girls (Gushue & Whiston, 2006) and to engagement in career exploration activities and a clearer sense of vocational goals, strengths, and interests among a sample of Latina/Latino high school students (Gushue, Clarke, Pantzer, & Scanlan, 2006). In addition, Flores and O'Brien (2002) found that Mexican American adolescent women's confidence in their abilities to succeed in nontraditional female occupations was positively associated with nontraditional female career interests, career choice traditionality, and career choice prestige.…”
mentioning
confidence: 92%